1996
DOI: 10.1097/00007890-199605270-00015
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bone Loss in Cardiac Transplant Recipients

Abstract: Bone mineral density is already abnormally reduced at the moment of cardiac transplantation and bone loss occurs at an impressive rate in the first postoperative year. The aim of the study was to compare two prophylactic medical regimens as to their efficacy in mitigating bone loss after transplantation. Forty-eight consecutive recipients were randomized to receive either alternating calcium carbonate and disodium etidronate (group A) or a daily supplement of calcium carbonate and alphacalcidol (group B). Bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 16 publications
6
45
1
4
Order By: Relevance
“…Consistently with these findings, our group have found that in patients randomized immediately after cardiac transplantation to 32000 IU/week of oral calcidiol for 18 months, lumbar spine BMD increased 5%, whereas those who received cyclical etidronate or nasal calcitonin, showed decreases in spine BMD (Garcia-Delgado et al, 1997). Also, alfacalcidol therapy has been associated with an increase in BMD or prevention of additional bone loss in renal (El-Agroudy et al, 2003) and cardiac recipients ( Van Cleemput et al, 1996).…”
Section: Calcidiol (25-hydroxivitamin D) and Alfacalcidol (1-hydroxisupporting
confidence: 67%
“…Consistently with these findings, our group have found that in patients randomized immediately after cardiac transplantation to 32000 IU/week of oral calcidiol for 18 months, lumbar spine BMD increased 5%, whereas those who received cyclical etidronate or nasal calcitonin, showed decreases in spine BMD (Garcia-Delgado et al, 1997). Also, alfacalcidol therapy has been associated with an increase in BMD or prevention of additional bone loss in renal (El-Agroudy et al, 2003) and cardiac recipients ( Van Cleemput et al, 1996).…”
Section: Calcidiol (25-hydroxivitamin D) and Alfacalcidol (1-hydroxisupporting
confidence: 67%
“…Additional treatment such as biologically active vitamin D preparations or new effective bisphosphonates require testing in further studies. The former has been of benefit in patients receiving corticosteroid treatment 28 in association with organ transplants 29 and a preliminary report confirms benefits provided by bisphosphonates in organ transplant recipients. 30 …”
Section: Discussionmentioning
confidence: 68%
“…However, despite the use of lower maintenance doses of corticosteroids, as a result of the use of CsA, a decrease of early posttransplantation bone loss has not been observe as a result of an imbalance in bone remodeling consistent with the toxic effects of steroids (3). In renal transplant recipients, posttransplantation bone loss is more complex (18). Pretransplantation renal osteodystrophy and persistent hyperparathyroidism are still risk factors.…”
Section: Discussionmentioning
confidence: 99%